Sustainable Development Goal 6: ensuring the availability and sustainable management of water and sanitation for all - van Koppen, Barbara (Edward Elgar Publishing, 2024)
Sustainable Development Goal 6 (SDG6) seeks to ‘ensure availability and sustainable management of water and sanitation for all’, and addresses the pathways to health, hygiene and ending hunger. This chapter highlights how reliable, weather-proof access to water is key for drinking, domestic uses, hygiene, and food preparation and processing from household to industrial scales. Further, agricultural water management and irrigation improve crop yields and can extend cropping into the ‘hunger’ season, also overcoming unexpected droughts. Moreover, water security stimulates investments in higher-value seeds and other inputs. Livestock, fisheries and aquaculture also depend on water availability. These pathways contribute to higher dietary diversity of micro-nutrient and protein-rich vegetables, meat, eggs, and other food for own consumption or sale. Water availability for multiple uses at homesteads is particularly effective for ending child malnutrition. However, food systems also risk polluting water. Therefore, SDG6 also envisages water quality control and resource recovery.